EVALUATION OF TEST CROSSES A WAY FORWARD TOWARDS THE IDENTIFICATION OF POTENTIAL RESTORERS & MAINTAINERS FOR THE DEVELOPMENT OF RICE HYBRIDS - BIBI, T; BIBI, A; LATIF, T; SABAR, M; ALI, SS; RIAZ, M; RIAZ, A; NAWAZ, A (Biological and Clinical Sciences Research Journal, 2023)
Identification of desirable maintainers and potential restorers in a hybrid rice breeding program is the dire need for the development of potential rice hybrids. Seventeen (17) cytoplasmic male sterile (CMS) lines (15 imported from IRRI and 02 locally developed by RRI, KSK) of rice were crossed with one hundred and sixty (160) testers to identify their genetic nature to behave as restorer or maintainer in the year 2017 and 2018. A total of one hundred and sixty (160) rice test crosses were subjected to pollen and spikelet fertility when crossed with CMS lines. Most of the testers show differential fertility/sterility responses with CMS lines. From these evaluated test crosses thirty-three (33) restorers and thirty-four (34) maintainers (16 Basmati and 18 non-basmati lines) were recognized for further use to develop potential rice hybrids. Four basmati and twenty-nine coarse lines were identified as restorers from the tested genotypes. Most of the genotypes found to be partial restorer (PR) and partial maintainers (PM). Moreover, four promising heterotic combinations/potential restorers were also identified. Six heterotic hybrid combinations had more than 80% spikelet fertility. Potential restorers and maintainers identified in the present exploration could be used to develop high-yielding promising rice hybrids adaptable to the diversified climatic conditions of Punjab, Pakistan.